Changes in involvement in homework throughout compulsory secondary education - Regueiro, Bibiana (2017)
This paper analyses the changes found in students' involvement in homework throughout the four grade levels of compulsory secondary education in Spain (ages 12-15). It also analyses the relationship between the changes in students' involvement in homework throughout schooling and motivational and emotional variables related to homework. Findings indicated that: (a) the amount of homework completed and homework time management diminished slightly throughout the grade levels researched; however, this result is clearer in terms of the amount of homework completed; (b) prior academic achievement is significantly related to the variables associated with students' involvement in homework; (c) the motivational and affective variables researched explained statistically significant variance related to two of the three dependent variables associated with involvement in homework; and (d) the association between the motivational and affective variables and involvement in homework is lower.